2002
DOI: 10.1103/physrevlett.89.135501
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of Reconstruction of Multiphase Morphologies from Two-Point Correlation Functions

Abstract: The restoration of the spatial structure of heterogeneous media, such as composites, porous materials, microemulsions, ceramics, or polymer blends from two-point correlation functions, is a problem of relevance to several areas of science. In this contribution we revisit the question of the uniqueness of the restoration problem. We present numerical evidence that periodic, piecewise uniform structures with smooth boundaries are completely specified by their two-point correlation functions, up to a translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 33 publications
0
34
1
Order By: Relevance
“…Although there has been significant progress on reconstruction algorithms [1,[14][15][16], it remains a challenge to reconstruct accurately percolating microstructures, sets of essentially zero measure (e.g., cracked media and filamentary structures), and multiply connected microstructures. In this paper we introduce a procedure that enables one to begin to reconstruct such microstructures with heretofore unattained accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been significant progress on reconstruction algorithms [1,[14][15][16], it remains a challenge to reconstruct accurately percolating microstructures, sets of essentially zero measure (e.g., cracked media and filamentary structures), and multiply connected microstructures. In this paper we introduce a procedure that enables one to begin to reconstruct such microstructures with heretofore unattained accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the structural ambiguity is considerably larger for a radial function without angular information, which is the only data available from small-angle scattering experiments. However, if angular information is employed successful microstructure reconstructions can often be obtained [18][19][20][21].…”
Section: S T R I B Umentioning
confidence: 99%
“…While models must be formulated and applied at macroscopic length scales that range from meters to kilometers, it is known that the microscopic arrangement of fluids within geologic materials has important consequences for fluid flow [12][13][14][15][16][17][18][19][20][21][22]. In particular, the snapoff and entrapment of fluid sub-regions at the pore-scale has been established as an important source of hysteresis [23][24][25][26][27].…”
mentioning
confidence: 99%